Prognostic and immunological role of cuproptosis-related protein FDX1 in pan-cancer - Xiao, Chen; Yang, Linhui; Jin, Liangzi; Lin, Weiguo; Zhang, Faqin; Huang, Shixin; Huang, Zhijian (Frontiers in Genetics, 2022)
Abstract Background: Cancer is the 2nd death cause worldwide. copperoptosis is a new mode of regulated cell death, and copperoptosis is strongly associated withmetabolic pathways. FDX1 is a key gene that promotes copperoptosis, and its impact on tumor pathogenesis and tumor immune response is indistinct and needs further exploration. Methods: By mining the Cancer Genome Atlas （TCGA） database, the Broad Institute Cancer Cell Line Encyclopedia (CCLE) database and the International Cancer Genome Consortium (ICGC), including the information of clinic and mutation. Survival analyses included the Kaplan-Meier method for calculating the cumulative incidence of survival events and the log-rank method for comparing survival curves between groups. Immune cell infiltration levels were calculated using the Spearman correlation test and correlated with FDX1 expression to assess significance. More correlation analyses between FDX1 expression and mutational markers, such as tumor mutational burden (TMB) and microsatellite instability (MSI), were also examined by Spearman assay. And to explore the relation between FDX1 expression and the sensitivity of common antitumor drugs. Results: FDX1 expression was down-regulated in most kinds of cancers, and this high expression indicated better overall survival (OS) and death-specific survival. For several cancer types, FDX1 expression had positive correlation with immune cell infiltration, and FDX1 also had positive correlation with TMB and MSI in some cancer types, linking its expression to the assessment of possible treatment response. Conclusions: The correlations between FDX1 expression and cancer in kinds of tissues, including clear links to cancer survival and prognosis, make cancer surveillance and further research have an interesting biomarker and potential therapeutic target for.